653 Safety for youth involved in community based agriculture. (1st September 2016) - Salzwedel, Marsha; Weichelt, Bryan; Bendixsen, Casper; Lee, Barbara C
Abstract : Background: As Community Based Agriculture (CBA) gains popularity in the U.S., more youth are becoming involved. One type of CBA is Community Supported Agriculture (CSA). In CSA, farms sell shares of their harvest, which may include customer labour: as part of the share, to reduce the price of the share, or to gain extra product. Another form of CBA is public gardens (e.g., community, urban, school). Adults work with youth to plant, weed and harvest. Often, those working in CBA are not familiar with the tasks, equipment, and hazards. There are no known safety resources for youth involved in CBA, thus adults depend on prevention strategies from various disciplines to address common problems such as bee stings or weather-related hazards. Methods: A pilot study was undertaken to assess youth safety in CBA. A survey was sent to a convenience sample of community/school garden organisers to learn more about youth working in gardens, the types of jobs they perform, the types of equipment being used, and the injuries and illnesses that occur. Eighteen completed surveys were returned and analysed, representing a variety of operations. Results: Survey results revealed many groups engage youth in CBA, and youth perform a wide variety of tasks. Very few have formal safety programs; all desire more safety information. In response, "Community-Based Agriculture: Safety Guidelines for Youth Working in Gardens" was developed. Content is based on the North American Guidelines for Children's Agricultural Tasks and Safety Guidelines for Hired Adolescent Farm Workers. Dissemination efforts included press releases, Ag Educator listservs, and social media. Over 1000 booklets have been distributed, and links are on several national websites. Conclusions: In the U.S., CBA activities offer an opportunity for safety professionals to engage with community programs and embed effective principles to safeguard youth. This is especially important, given the national push to grow and eat natural foods.